2020
DOI: 10.3390/nu12071909
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K Nutrition and Bone Health

Abstract: Vitamin K is essential for blood coagulation and plays an important role in extrahepatic metabolism, such as in bone and blood vessels, and in energy metabolism. This review discusses the assessment of vitamin K sufficiency and the role of vitamin K in bone health. To elucidate the exact role of vitamin K in other organs, accurate tools for assessing vitamin K deficiency or insufficiency are crucial. Undercarboxylated vitamin K-dependent protein levels can be measured to evaluate tissue-specific vitamin K defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 79 publications
1
33
0
2
Order By: Relevance
“…This study provides a framework for future studies, both in vitro and in vivo for the role of MK-7 in bone formation and fracture healing. This corroborates observations, from longitudinal and interventional trials on increased bone mineral density following either vitamin K2 supplementation (Sato et al, 2020 ) or an increased amount of vitamin K2 in the diet (Tsugawa and Shiraki, 2020 ). Furthermore, the role of VKDPs in iPSC derived products has not been widely explored.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study provides a framework for future studies, both in vitro and in vivo for the role of MK-7 in bone formation and fracture healing. This corroborates observations, from longitudinal and interventional trials on increased bone mineral density following either vitamin K2 supplementation (Sato et al, 2020 ) or an increased amount of vitamin K2 in the diet (Tsugawa and Shiraki, 2020 ). Furthermore, the role of VKDPs in iPSC derived products has not been widely explored.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, we interrogated the differentiation trajectory, given basic and clinical science reports on pro-osteogenic properties of MK-7, such as promoting bone formation, bone density and strength, as well as inhibiting bone loss (Sato et al, 2020 ). Furthermore, vitamin K deficiency is associated with increased fracture rate and decreased bone mass density in a variety of patient cohorts (Tsugawa and Shiraki, 2020 ). Therefore, we determined whether MK-7 supplementation may further propagate an osteogenic phenotype of iMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Bone strength is determined by bone mineral content (BMC) and its quality and is associated with biological senescence and vitamin (B, D, K) deficiencies. As VK activates tissue-specific VKDPs, such as prothrombin, OC, or MGP, via the γ-carboxylation of Glu to Gla molecules, insufficient VKDPs γ-carboxylation is a sensitive, tissue-specific marker of VK deficiency [40]. Several studies revealed that VK is involved in bone metabolism and inhibits bone resorption in a dose-dependent manner.…”
Section: Vitamin K In Bone Healthmentioning
confidence: 99%
“…Third, vitamin K status, which is known to affect OC carboxylation, has not been evaluated in the present series due to unavailability of accurate tools such as high-performance liquid chromatography–tandem mass spectrometry for the assessment of vitamin K homologues, phylloquinone (vitamin K1) and menaquinones (MK-4 and MK-7). However, it is of note that measuring uncarboxylated vitamin K-dependent protein (i.e., osteocalcin) levels is considered the most accurate and convenient method for assessing tissue-specific vitamin K deficiency or insufficiency ( 56 ). Indeed, here failure in detecting association between plasma uOC levels and most of the parameters related with body composition, may suggest that vitamin K replenishment is not a major determinant of the potential relationship with muscle mass and function.…”
Section: Discussionmentioning
confidence: 99%